신혼가구의 주거 입지에 나타나는 세대간 시간 자원의 이전과 성별 효과 - 이길제(Lee Gil Jae); 최막중(Choi, Mack Joong) (국토계획, 2017)
본 연구는 신혼가구의 주거 입지에 있어부모와의 지리적 근접 여부에 의해 나타나는 세대간 시간 자원 이전의 효과를 실증적으로 분석하는데 목적이 있다. 구체적으로 연구질문은 자녀와 부모의 시간 지원에 대한 요구(needs)가 자녀가구와부모가구 주택의 지리적 근접 여부에 어떠한 영향을 미치는지, 그리고 그러한 영향이 남녀 부모에따라 어떻게 다르게 나타나는지로 구성된다. 분석자료는 한국노동패널조사(KLIPS) 자료에서 결혼으로인한 분가가구를 추출하여 구성하며, 남녀집단으로구분하여 비교한다. 분석모형으로는 지리적 근접성을 동일 시군구의 거주 여부로 측정하여 분가시점에서 이항로짓모형을 적용하고. 시간의 흐름에 따른출산과 육아 등의 생활여건 변화를 반영하기 위해분가 후 5년까지의 신혼가구를 대상으로 패널이항로짓모형으로 확장한다. 이후 제Ⅱ장에서는 세대간 시간 자원 이전에 관한 이론 및 선행연구를 고찰하고, 제Ⅲ장에서 분석자료 및 분석방법과 모형 등에 관한 분석틀을 정립한다. 제Ⅳ장에서는 이항로짓모형과 패널이항로짓모형을 통해 부모와 자녀가구 주택의 지리적 근접 여부에 영향을 미치는 요인들을 추정하고 그 의미를해석한다. 제Ⅴ장에서는 분석결과를 종합하고 결론을 맺는다. The recent study empirically confirms intergenerational transfer of asset and its gender effect in Korea, as parents’ wealth affects their child’s housing asset prepared for marriage while bridegroom’s parents take a leading role. In comparison, this study investigates how intergenerational transfer of time resource takes place in association with the needs of newly married households for housework and childrearing as well as the parents’ needs for caring for the elderly, paying attention to the difference of role between bride’s and bridegroom’s parents. Since the transfer of time requires a geographical proximity, the probability is approximated by that of parents’ and child’s residences located in the same administrative district. The estimation results of logit and panel logit models based on the survey data of Korean Labor and Income Panel Study demon Strate that the child’s needs make their residence close to that of bride’s parents and the probability of co-location increases during the childrearing period compared to the time of child’s moving out. The transfer of child’s time to bride’s parents also takes place as parents become older and unhealthier. While these results verify that intergenerational transfer of time occurs centering around bride’s parents, only the wealth of bridegroom’s parents make child’s residence close to their residence at the time of moving out, which might be related to the transfer of asset. KCI Citation Count: 7